The Role of Social Stereotypes in Shaping Opportunities and Inequalities in Society: Their Impact on Education, Employment, and Intergroup Interactions - Sajjapong, Thanawat; Darmawan, Didit; Marsal, Antonino Pedro (Bulletin of Science, Technology and Society, 2022)
Social stereotypes, both positive and negative, play an important role in shaping individual perceptions and interactions between groups in society. These stereotypes often limit social, educational, and employment opportunities for stereotyped individuals, exacerbate social inequalities, and increase discrimination. In an educational perspective, for example, stereotypes can hinder individual academic performance, especially in minority groups that are stereotyped as less capable. In the world of work, stereotypes can also affect the selection and promotion process so that stereotyped groups are often overlooked even though they have equivalent qualifications. In addition, social stereotypes exacerbate social polarization by creating greater gaps between groups and hindering the process of fairer social integration. For this reason, it is important to understand how social stereotypes can affect individual opportunities and well-being and how they contribute to existing social inequalities. This article proposes an education-based approach and inclusive policies to reduce the negative impact of social stereotypes, which is expected to encourage more positive interactions between groups and improve existing gaps in society. This study identifies the importance of deconstructing social stereotypes to create a more inclusive, fair, and equal society.